(untitled) (Bangladesh Journal of Public Administration, 2025)
Cyberbullying constitutes a form of online activity characterized by intentional and repetitive actions aimed at causing harm, harassment, intimidation, or humiliation to an individual. It is associated with a host of challenges, such as low self-esteem, social isolation, depression, emotional distress, and poor academic results. With the advent of advanced technology, the ramifications of cyberbullying have escalated considerably. This research endeavours to examine the social and psychological ramifications of cyberbullying on university students in Bangladesh. The investigation also evaluated the impact of cyberbullying on students’ academic performance and portrayed recommendations for enhancing the situation within the relevant domain. However, a self-structured questionnaire was constructed to collect data through the survey method. In addition to the survey, a questionnaire was created using Mail Questinnaire to expand the reach to a broader spectrum of respondents. 210 questionnaires were collected for the study using the purposive sampling technique. Both primary data and secondary data have been used to fulfil the objective. As primary data, interviews with the victims among the students have been taken, and as secondary data, various articles and reports have been reviewed. SPSS Version 22 was employed for data analysis. This research has identified that students are subject to diverse forms of cyberbullying, resulting in a range of social, psychological, and academic difficulties. These challenges exert adverse effects on their lives across multiple dimensions. Additionally, the investigation reveals that victims of cyberbullying often confide in peers who are unable to offer practical solutions. This study has embodied some recommendations that will unlock ways to improve this area. The study implies that university authorities should launch extensive awareness efforts and educational programmes to teach students how to prevent and respond to cyberbullying. Universities may need to allocate resources to establish mental health and support services to assist those affected by cyberbullying, as it is evident from this study that the mental health and well-being of students are at stake.